Intratracheal cell transfer demonstrates the profibrotic potential of resident fibroblasts in pulmonary fibrosis - Tsukui, Tatsuya; Ueha, Satoshi; Shichino, Shigeyuki; Inagaki, Yutaka; Matsushima, Kouji (The American journal of pathology, 2015)
Pulmonary fibrosis is a devastating disease for which there are few effective therapies. Activated fibroblasts form subepithelial clusters known as fibroblastic foci, which are characterized by excessive collagen deposition. The origin of activated fibroblasts is controversial and needs to be clarified to understand their pathogenicity. Here, using an intratracheal adoptive cell transfer method, we show that resident fibroblasts in alveolar walls have the highest profibrotic potential. By using collagen I(α)2-green fluorescent protein and neural/glial antigen 2-DsRed fluorescent reporter mice, we identified resident fibroblasts and pericytes in the alveolar walls based on surface marker expression and ultrastructural characteristics. In the early phase of bleomycin-induced pulmonary fibrosis, activated fibroblasts migrated into epithelium-denuded alveolar airspaces. Purified resident fibroblasts delivered into injured alveoli by an intratracheal route showed similar activated signatures as activated fibroblasts and formed fibroblastic foci. Neither pericytes nor epithelial cells had the same profibrotic potential. Transferred resident fibroblasts highly up-regulated profibrotic genes including α-smooth muscle actin and were a significant source of collagen deposition. These data provide insights into the cellular mechanisms of fibrogenesis and show intratracheal cell transfer to be a useful tool for exploring novel therapeutic targets against pulmonary fibrosis.